(untitled) (Fiep Bulletin - online, 2011)
Cardiovascular diseases are prevalent in the elderly due to morphological, physiological and behavioral interviews. As the use of drug therapy of the main treatments prescribed in the treatment of cardiovascular diseases. Knowledge of pharmacokinetics and pharmacodynamics appears to be of great importance, particularly for nurses, as well as the changes of aging, there are chronic pathological processes and possibly acute illnesses associated with the use of drugs. The cardiotonic glycosides deserve special attention by the nursing staff, because it is a drug that has a narrow therapeutic window and increased half life in the elderly is common toxicity of this drug even with therapeutic doses usually aim of this study was to identify the knowledge of the team nurses included nurses, technicians and nursing assistants on the use of digitalis in elderly patients in the intensive care unit and cardiology which the nursing care provided in intensive care for the elderly that makes this drug. Descriptive study, based on qualitative. The study included ten members of the nursing staff working in the intensive care unit cardiac included nurses, practical nurses and nursing assistants during the data collection along with the nursing staff who experience, prepares and administers the digitalis was found concern for the team in understanding the effect of this drug in the elderly because of the mechanism of absorption, distribution, metabolism and excretion are altered with aging. And when it comes to the importance of recognition possible for signs of intoxication, it is vital to the preparation of nursing staff in the evaluation of main signs and symptoms during this episode.